Effect of Extraction Condition of Natural Dye Pigment from Bougainvillea Flowers’ Bract - Nur Athirah, Sabarudin; Mimi Sakinah, A. M.; Zularisam, A. W. (AENSI Publishing, 2016)
Bougainvillea is known as a garden flower which is red in color that contains betacyanin, a betalain pigment. Recently, betacyanin is becoming an increasingly popular active ingredient as a dye especially in textile and food industries. This pigment has acquired greater significance because of its excellent color value. However, the use of bougainvillea as a natural textile colorant is still uncommon. This is due to the lack of information on its stability and compatibility in textile dyeing. In this study, solvent extraction was conducted to investigate the factors contributing for pigment extraction from the flowers’ bracts. Solid-liquid ratio (SLR) and extraction time were investigated. The color intensity of the dye was evaluated using UV-Vis spectrophotometer. The findings show that both parameters displayed significant effects on the extraction process. The process was better in acidic condition than in alkaline, with a solid-liquid ratio of 0.1. The equilibrium time was reached after 60 minutes of the extraction process. These findings reveal that pigment from Bougainvillea flowers’ bracts can be extracted with convenient condition of SLR and equilibrium time